A BOPP laser film with stable aluminum layer surface tension and preparation method thereof

By selecting the appropriate molecular weight distribution index of ethylene-propylene binary copolymer polypropylene in the BOPP laser film and setting a polar adsorption layer, the problem of surface tension attenuation of the aluminum layer is solved, and the stability of surface tension and the improvement of processing performance is achieved.

CN119036981BActive Publication Date: 2024-12-31GUANGDONG DECRO PACKAGE FILMS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411553800.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2024-12-31
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing BOPP laser film attenuates the surface tension below 38mN/m, which cannot stably meet the downstream customers' processing needs for printing ink or glue coating. The main reason is that excessive corona treatment leads to migration of low molecular substances, resulting in surface tension of aluminum layer. Unstable.

Method used

By selecting the molecular weight distribution index of ethylene-propylene binary copolymer polypropylene in the molded layer to be 4-5, the production of low molecular substances is reduced, and the polarity and adsorption are set in the last and next surface layers, and the adsorption is low. Molecular substances reduce their migration and ensure the stability of the surface tension of the aluminum layer.

Benefits of technology

It achieves stability of the surface tension of the aluminum layer, reduces haze and heat shrinkage, improves gloss and production smoothness, and meets the downstream customers' needs for processing BOPP laser film after aluminum plating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the field of films, and in particular to a BOPP laser film with a stable surface tension of an aluminum layer and a preparation method thereof, wherein the BOPP laser film comprises a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer which are arranged in sequence; the molded layer comprises ethylene-propylene binary copolymer polypropylene, the molecular weight distribution index of the ethylene-propylene binary copolymer polypropylene is 4-5, the upper surface layer comprises 100.0wt% modified ethylene-propylene binary copolymer polypropylene, the core layer comprises homopolymer polypropylene, the lower surface layer comprises 100.0wt% modified homopolymer polypropylene, and the lower surface layer comprises homopolymer polypropylene. On the one hand, the present invention is conducive to reducing the generation of low-molecular substances in the molded layer by specifically selecting the molecular weight distribution index of the ethylene-propylene binary copolymer polypropylene in the molded layer; on the other hand, by setting the upper surface layer and the lower surface layer with polarity and adsorption as adsorption layers of low-molecular substances, the migration of low-molecular substances to the surface of the film, especially the molded layer, is reduced, and the synergistic effect ensures the stability of the surface tension of the BOPP laser film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of films, and in particular to a BOPP laser film with stable aluminum layer surface tension and a preparation method thereof. Background Art

[0002] Biaxially oriented polypropylene (BOPP) laser film is a BOPP film with unique charm and wide application prospects. It is generally made of a molded layer, a core layer, and a light layer through co-extrusion and biaxial stretching. The surface of the BOPP laser film has been specially treated to reflect rainbow-like laser light. At different angles and light, the colors and patterns are unpredictable, presenting a colorful visual effect, giving people a strong visual impact; BOPP laser film is used for packaging of food, medicine, cosmetics, gifts and other products, as well as in decorative materials and labels. It can not only improve the grade and added value of the product, but also add more color and creativity to people's lives, and can also play a role in anti-counterfeiting and promotion.

[0003] Normally, when downstream customers process BOPP laser film, they will further form an aluminum layer by aluminizing the molded layer after molding, and then further process the aluminized BOPP laser film according to the needs of different products. In order to ensure that downstream customers can smoothly process the aluminized BOPP laser film, the current BOPP laser film generally uses homopolymer polypropylene and copolymer polypropylene without low molecular weight additives as raw materials to reduce the migration of low molecular weight substances to the surface of the aluminum layer, which causes the surface tension of the aluminum layer to decay too quickly.

[0004] However, under the premise of using homopolymer polypropylene and copolymer polypropylene without low molecular weight additives as raw materials, the existing BOPP laser film still cannot stably meet the processing needs of some downstream customers for printing ink or coating glue on the outer surface of the aluminum layer. After analysis, the inventor found that the direct reason is that the surface tension of the aluminum layer decays to below 38mN / m, while printing ink or coating glue on the outer surface of the aluminum layer requires the surface tension of the aluminum layer to be ≥38mN / m. The fundamental reason is the excessive corona treatment of the laser film by downstream customers.

[0005] Corona treatment is to generate a high-energy electric field on the surface of the film to ionize molecules such as oxygen in the air to form active oxygen and other substances. These active substances will react with the polymer molecules on the surface of the film, thereby increasing the surface tension of the film. Specifically, a large number of plasma particles and ozone are generated during corona treatment. They directly or indirectly react chemically with the copolymerized polypropylene molecules on the corona surface and the water in the air, introducing polar oxygen-containing groups such as C=O and -OH, increasing the number of polar molecules on the surface, thereby increasing its surface tension.

[0006] The products processed by downstream customers are relatively diverse, and different products have different requirements for corona power. For the sake of ease of operation, ensuring smooth production, and reducing the cost of adjusting process parameters, some downstream customers will directly perform high-power corona treatment on all products to ensure that the surface tension of the products after corona treatment must increase to meet their subsequent production and processing needs; this production and processing strategy leads to excessive corona treatment of BOPP laser film. In the case of excessive corona treatment, the concentration of substances such as active oxygen in the laser film is too high, and the reaction activity is enhanced, which will attack the low molecular weight part of the copolymer polypropylene molecular chain in large quantities, causing the molecular chain to break, and accelerating the process of copolymer polypropylene molecule degradation to produce low molecular weight substances. Since low molecular weight substances have strong mobility and tend to migrate from high concentration to low concentration, these low molecular weight substances migrate to the surface of the aluminum layer with relatively lower concentration, causing the surface tension of the aluminum layer to decay to below 38mN / m, which cannot stably meet the processing needs of some downstream customers for printing ink or coating glue on the outer surface of the aluminum layer. Summary of the invention

[0007] Based on this, the purpose of the present invention is to provide a BOPP laser film with stable surface tension of the aluminum layer. On the one hand, by specifically selecting the molecular weight distribution index of ethylene-propylene binary copolymer polypropylene in the molded layer, it is beneficial to reduce the generation of low molecular weight substances in the molded layer; on the other hand, by setting the upper surface layer and the lower surface layer with polarity and adsorption as the adsorption layer of low molecular weight substances, the migration of low molecular weight substances to the surface of the film is reduced, especially the migration of low molecular weight substances to the molded layer and the aluminum layer is reduced. The synergistic effect ensures the stability of the surface tension of the BOPP laser film and the stability of the surface tension of the aluminum layer after the BOPP laser film is aluminized. The prepared BOPP laser film has the advantages of stable surface tension, low haze, high gloss, low heat shrinkage and smooth production.

[0008] The technical solution of the present invention is achieved by the following methods:

[0009] A BOPP laser film with stable aluminum layer surface tension comprises a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer which are arranged in sequence; the molded layer comprises ethylene-propylene binary copolymer polypropylene, the molecular weight distribution index of the ethylene-propylene binary copolymer polypropylene is 4-5, and the molecular weight distribution index=weight average molecular weight / number average molecular weight; the upper surface layer comprises 100.0wt% modified ethylene-propylene binary copolymer polypropylene, the modified ethylene-propylene binary copolymer polypropylene comprises ethylene-propylene binary copolymer polypropylene-g-polyacrylic acid copolymer; the core layer comprises homopolypropylene; the lower surface layer comprises 100.0wt% modified homopolypropylene, the modified homopolypropylene comprises homopolypropylene-g-polyacrylic acid copolymer; and the lower surface layer comprises homopolypropylene.

[0010] The BOPP laser film with stable surface tension of the aluminum layer described in the present invention, on the one hand, is beneficial to reduce the generation of low molecular weight substances in the molded layer by specifically selecting the molecular weight distribution index of ethylene-propylene binary copolymer polypropylene in the molded layer; on the other hand, by setting the upper surface layer and the lower surface layer with polarity and adsorptivity as adsorption layers for low molecular weight substances, the migration of low molecular weight substances to the surface of the film is reduced, especially the migration of low molecular weight substances to the molded layer is reduced, and the synergistic effect ensures the stability of the surface tension of the BOPP laser film, and also ensures the stability of the surface tension of the aluminum layer after the BOPP laser film is aluminized. The prepared BOPP laser film has the advantages of stable surface tension, low haze, high gloss, low heat shrinkage rate and smooth production.

[0011] The molded layer of the BOPP laser film with stable aluminum layer surface tension described in the present invention adopts ethylene-propylene binary copolymer polypropylene with a molecular weight distribution index of 4-5, which reduces the generation of low-molecular substances in the molded layer. On this basis, if the molecular weight distribution index of ethylene-propylene binary copolymer polypropylene is less than 4, the melt viscosity of the material is relatively high, the fluidity is poor, the melt film forming property is poor, and the phenomenon of poor molding is easy to occur during the production process; if the molecular weight distribution index of ethylene-propylene binary copolymer polypropylene is greater than 5, the heat resistance and aging resistance of the material are poor, resulting in problems such as sticking to the roller after preheating or oxidative aging during the downstream use of the BOPP laser film. At the same time, it means that there are a large proportion of low molecular weight parts and high molecular weight parts in the copolymer polypropylene, and the molecular chain of the low molecular weight part is shorter and relatively unstable. It is more likely to degrade under external effects such as corona treatment, resulting in the precipitation of low molecular weight substances, which is more unfavorable for surface tension stability.

[0012] After the molded layer of the BOPP laser film with stable aluminum layer surface tension described in the present invention is subjected to excessive corona treatment, since the concentration of low-molecular substances in the upper surface layer is lower than that in the molded layer, the low-molecular substances produced by the molded layer tend to migrate to the upper surface layer, and the polarity and adsorption of the upper surface layer enable it to absorb more low-molecular substances. After the BOPP laser film with stable aluminum layer surface tension is aluminized, although the aluminum layer and the molded layer will also form a concentration difference causing low-molecular substances to migrate to the aluminum layer, the upper surface layer has been continuously absorbing low-molecular substances produced after corona treatment before aluminization, and the amount of low-molecular substances that can migrate to the aluminum layer is relatively small, so the surface tension of the aluminum layer will not decrease too much, and will eventually tend to be stable. Similarly, the lower surface layer adsorbs the low-molecular substances produced by the corona treatment of the lower surface layer or the low-molecular substances produced by the normal degradation of the lower surface layer, reducing the migration of low-molecular substances produced in the lower surface layer to the surface of the aluminum layer layer by layer.

[0013] Furthermore, the thickness of the upper surface layer and the lower surface layer are both 0.7-0.9 μm, and the thickness of the molded layer is 0.7-0.9 μm. By combining the 0.7-0.9 μm molded layer containing ethylene-propylene copolymer polypropylene and the 0.7-0.9 μm upper surface layer containing modified ethylene-propylene copolymer polypropylene, a heat-sealing layer with a thickness of 1.4-1.8 μm is formed, which can effectively ensure the thickness of the heat-sealing layer, and then ensure the heat-sealing strength, thereby ensuring the molded laser effect, while ensuring the effective adsorption of low-molecular substances and controlling costs.

[0014] Furthermore, the weight average molecular weight of the ethylene-propylene binary copolymer polypropylene is 150,000-250,000 g / mol. When the weight average molecular weight of the ethylene-propylene binary copolymer polypropylene is greater than 250,000 g / mol, the molecular chains with high molecular weight are more tightly entangled with each other, making it difficult to stretch during the production process, and the long-chain molecules need to absorb more energy to melt, and the fluidity of the melt deteriorates, making production more difficult and affecting the smoothness of production; when the weight average molecular weight of the ethylene-propylene binary copolymer polypropylene is less than 150,000 g / mol, it will lead to greater thermal shrinkage during subsequent processing, affecting the use of customers.

[0015] Furthermore, the number average molecular weight of the ethylene-propylene binary copolymer polypropylene is 30000-60000 g / mol. The number average molecular weight of the ethylene-propylene binary copolymer polypropylene is greater than 60000 g / mol, the crystallinity of the material is too high, the molecular chain is long, and the molecular movement is greatly hindered. Long-chain molecules need longer time to adjust the conformation and form crystal nuclei during the crystallization process, so the crystallization speed slows down, the crystallinity is low, and during the stretching process, it is easy to cause uneven thickness and excessive deformation to cause film breakage; the number average molecular weight of the ethylene-propylene binary copolymer polypropylene is less than 30000 g / mol, the molecular chain is short, and it is easier to form a regular arrangement, which allows the molecular chains to be more densely stacked during the crystallization process to form a higher crystallinity, which will make the product haze larger. In addition, excessive crystallinity may cause the film to break during the stretching process.

[0016] Furthermore, the modified ethylene-propylene binary copolymer polypropylene is prepared by ion grafting copolymerization of the ethylene-propylene binary copolymer polypropylene and polyacrylic acid, and the grafting rate of the polyacrylic acid in the modified ethylene-propylene binary copolymer polypropylene is 25-40%. The grafting rate of the polyacrylic acid is 25-40%. If the grafting rate is too low, the polarity and adsorption performance are weak, and the low molecular weight substances generated by excessive corona treatment cannot be effectively adsorbed; if the grafting rate is too high, too many polyacrylic acid segments destroy the original crystalline structure of polypropylene, so that the material's bearing capacity decreases, the mechanical properties of the product decrease, and the smoothness of production is affected. In addition, the thermal stability of the product decreases, and during the molding process, it is easy to cause excessive heat shrinkage, reduce the product width, and be inconsistent with the width of downstream customers' paper, resulting in the inability to perform subsequent processing.

[0017] The carboxyl group of polyacrylic acid can form hydrogen bonds with many low molecular weight substances. This hydrogen bonding effect enables low molecular weight substances to be tightly bound to polyacrylic acid molecules, thereby achieving an adsorption effect. At the same time, the presence of multiple hydrogen bonds can enhance the stability of this adsorption effect, allowing low molecular weight substances to gather around polyacrylic acid molecules. In addition, polyacrylic acid is a high molecular polymer with a certain stretching and curling morphology in its molecular chain system. When low molecular weight substances are close to polyacrylic acid, the steric hindrance of the polyacrylic acid molecular chain may have a restrictive effect on the low molecular weight substances. Low molecular weight substances may be trapped in the spatial structure of the polyacrylic acid molecular chain and surrounded in space by different parts of the molecular chain. This steric hindrance effect may assist hydrogen bonding and polar interactions, making it more difficult for low molecular weight substances to separate from the polyacrylic acid molecules, thereby enhancing the adsorption effect.

[0018] Furthermore, the modified homopolypropylene is prepared by ion grafting copolymerization of the homopolypropylene and polyacrylic acid, and the grafting rate of the polyacrylic acid in the modified homopolypropylene is 25-40%. The grafting rate of the polyacrylic acid is 25-40%. If the grafting rate is too low, the polarity and adsorption performance are weak, and the low molecular weight substances generated by excessive corona treatment cannot be effectively adsorbed; if the grafting rate is too high, too many polyacrylic acid segments destroy the original crystalline structure of polypropylene, so that the material's bearing capacity decreases, the mechanical properties of the product decrease, and the smoothness of production is affected. In addition, the thermal stability of the product decreases, and during the molding process, it is easy to cause excessive heat shrinkage, reduce the product width, and be inconsistent with the width of downstream customers' paper, resulting in the inability to perform subsequent processing.

[0019] Furthermore, the melt index of the EPDM and the modified EPDM are both 6-8 g / 10 min, the melting point of the EPDM is 138-142° C., and the melting point of the modified EPDM is 135-140° C., which is conducive to ensuring the matching with the actual production temperature and ensuring smooth production.

[0020] Furthermore, the melting point of the modified homopolypropylene is 170-180° C., and the melt index of the modified homopolypropylene is 2-4 g / 10 min, which is conducive to ensuring melt matching between the core layer and the lower surface layer and ensuring smooth production.

[0021] Furthermore, the initial heat sealing temperature of the ethylene-propylene binary copolymer polypropylene is 128-132°C, and the initial heat sealing temperature of the modified ethylene-propylene binary copolymer polypropylene is 115-117°C.

[0022] The present invention also provides a method for preparing a BOPP laser film with stable surface tension of an aluminum layer as described above, comprising the following steps: screening raw materials, stirring each layer of raw materials evenly according to a ratio, dropping the raw materials into an extruder after metering to form a homogenized melt, passing the melt through a filter and then through a die head for multi-layer co-extrusion, casting the melt according to a flat film method, and then quenching it into a thick sheet, the thick sheet is subjected to a biaxial stretching method of first longitudinal stretching and then transverse stretching to form a biaxially stretched film, the film is subjected to a corona treatment, a flame treatment, or a plasma treatment after cooling, and then rolled into a mother roll, and after an aging treatment, slitting it into a finished product.

[0023] In order to better understand and implement the present invention, the present invention is described in detail below. DETAILED DESCRIPTION

[0024] It should be clear that the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the embodiments of the present application.

[0025] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0026] The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. On the contrary, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims. In the description of the present application, it should be understood that the terms "first", "second", "third", etc. are only used to distinguish similar objects, and do not have to be used to describe a specific order or sequence, nor can they be understood as indicating or implying relative importance. For those of ordinary skill in the art, the specific meanings of the above terms in the present application can be understood according to the specific circumstances.

[0027] In addition, in the description of this application, unless otherwise specified, "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0028] It should be understood that the embodiments of the present application are not limited to the precise structure described above, and various modifications and changes can be made without departing from the scope thereof. The scope of the embodiments of the present application is limited only by the appended claims.

[0029] The BOPP laser film with stable surface tension of the aluminum layer of the present embodiment, on the one hand, helps to reduce the generation of low molecular weight substances in the molded layer by selecting the molecular weight distribution of ethylene propylene binary copolymer polypropylene in the molded layer; on the other hand, by setting the upper surface layer and the lower surface layer with polarity and adsorptivity as adsorption layers for low molecular weight substances, the migration of low molecular weight substances to the surface of the film is reduced, especially the migration of low molecular weight substances to the molded layer and the aluminum layer is reduced. The synergistic effect ensures the stability of the surface tension of the BOPP laser film and the stability of the surface tension of the aluminum layer after the BOPP laser film is aluminized. The prepared BOPP laser film has the advantages of stable surface tension, low haze, high gloss, low heat shrinkage rate and smooth production.

[0030] Furthermore, the thickness of the upper surface layer and the lower surface layer are both 0.7-0.9 μm, and the thickness of the molded layer is 0.7-0.9 μm. By combining the 0.7-0.9 μm molded layer containing ethylene-propylene copolymer polypropylene and the 0.7-0.9 μm upper surface layer containing modified ethylene-propylene copolymer polypropylene, a heat-sealing layer with a thickness of 1.4-1.8 μm is formed, which can effectively ensure the thickness of the heat-sealing layer, and then ensure the heat-sealing strength, thereby ensuring the molded laser effect, while ensuring the effective adsorption of low-molecular substances and controlling costs.

[0031] Furthermore, the weight average molecular weight of the ethylene-propylene binary copolymer polypropylene is 150,000-250,000 g / mol. When the weight average molecular weight of the ethylene-propylene binary copolymer polypropylene is greater than 250,000 g / mol, the molecular chains with high molecular weight are more tightly entangled with each other, making it difficult to stretch during the production process, and the long-chain molecules need to absorb more energy to melt, and the fluidity of the melt deteriorates, making production more difficult and affecting the smoothness of production; when the weight average molecular weight of the ethylene-propylene binary copolymer polypropylene is less than 150,000 g / mol, it will lead to greater thermal shrinkage during subsequent processing, affecting the use of customers.

[0032] Furthermore, the number average molecular weight of the ethylene-propylene binary copolymer polypropylene is 30000-60000 g / mol. The number average molecular weight of the ethylene-propylene binary copolymer polypropylene is greater than 60000 g / mol, the crystallinity of the material is too high, the molecular chain is long, and the molecular movement is greatly hindered. Long-chain molecules need longer time to adjust the conformation and form crystal nuclei during the crystallization process, so the crystallization speed slows down, the crystallinity is low, and during the stretching process, it is easy to cause uneven thickness and excessive deformation to cause film breakage; the number average molecular weight of the ethylene-propylene binary copolymer polypropylene is less than 30000 g / mol, the molecular chain is short, and it is easier to form a regular arrangement, which allows the molecular chains to be more densely stacked during the crystallization process to form a higher crystallinity, which will make the product haze larger. In addition, excessive crystallinity may cause the film to break during the stretching process.

[0033] Furthermore, the modified ethylene-propylene binary copolymer polypropylene is prepared by ion grafting copolymerization of the ethylene-propylene binary copolymer polypropylene and polyacrylic acid, and the grafting rate of the polyacrylic acid in the modified ethylene-propylene binary copolymer polypropylene is 25-40%.

[0034] Furthermore, the modified homopolypropylene is prepared by copolymerizing the homopolypropylene with polyacrylic acid through ion grafting, and the grafting rate of the polyacrylic acid in the modified homopolypropylene is 25-40%.

[0035] Furthermore, the melt index of the EPDM and the modified EPDM are both 6-8 g / 10 min, the melting point of the EPDM is 138-142° C., and the melting point of the modified EPDM is 135-140° C., which is conducive to ensuring the matching with the actual production temperature and ensuring smooth production.

[0036] Furthermore, the melting point of the modified homopolypropylene is 170-180° C., and the melt index of the modified homopolypropylene is 2-4 g / 10 min, which is conducive to ensuring melt matching between the core layer and the lower surface layer and ensuring smooth production.

[0037] Furthermore, the initial heat sealing temperature of the ethylene-propylene binary copolymer polypropylene is 128-132°C, and the initial heat sealing temperature of the modified ethylene-propylene binary copolymer polypropylene is 115-117°C.

[0038] Furthermore, the total thickness of the BOPP laser film with stable surface tension of the aluminum layer is 15-20 μm, and the thickness of the lower surface layer is 1.2-1.5 μm.

[0039] The invention also provides a method for preparing any of the above-mentioned BOPP laser films with stable surface tension of the aluminum layer, comprising the following steps: screening the raw materials, stirring the raw materials of each layer evenly according to the ratio, dropping the raw materials into an extruder after metering to form a homogenized melt, passing the melt through a filter and then through a die head for multi-layer co-extrusion, according to the flat film method, casting the film and then quenching it into a thick sheet, the thick sheet is subjected to a biaxial stretching method of first longitudinal stretching and then transverse stretching to form a biaxially stretched film, the film is subjected to corona treatment, flame treatment or plasma treatment after cooling, and then rolled into a mother roll, and after aging treatment, slitting into finished products.

[0040] Furthermore, the melt extrusion temperature of the molded layer is 200℃~250℃; the melt extrusion temperature of the upper surface layer is 200~220℃; the melt extrusion temperature of the core layer is 240℃~270℃; the melt extrusion temperature of the lower surface layer is 240-270℃; the melt extrusion temperature of the lower surface layer is 240℃~270℃; the temperature of the chilled water and the chilled roller is 15℃~50℃; the temperature of the longitudinal stretching zone (molded layer) is 110℃~120℃; the longitudinal stretching temperature (lower surface layer) is 135℃~155℃; the temperature of the transverse stretching zone is 140℃~180℃; the longitudinal stretching ratio is 4.5~5.0 times; the transverse stretching ratio is 6~8 times.

[0041] The physical properties and test methods of the embodiments or comparative examples of the present invention are as follows:

[0042] The melt index (melt mass flow rate MFR) is based on GB / T3682-2018, and homopolymer polypropylene and copolymer polypropylene are measured at 2.16 kg and 230°C.

[0043] Glossiness is tested according to GB / T8807-88 at a 45° angle.

[0044] Haze and light transmittance are tested according to GB / T2410-2008.

[0045] Weight average molecular weight, number average molecular weight, molecular weight distribution index, use gel permeation chromatography, grind the PP sample into small particles, add 1,2,4-trichlorobenzene, heat and stir at 130-150℃ to fully dissolve it, and filter it with a disposable microporous filter membrane after dissolution. After the instrument is stable, set the mobile phase speed to 1ml / min, and inject the polystyrene standard solution into the gel permeation chromatography for analysis. Record the elution time and corresponding molecular weight of each standard. Inject 50-100μL of the treated PP sample solution into the gel permeation chromatograph. Bubbles and leakage should be reduced during injection. According to the established calibration curve, the elution time of the PP sample is converted into molecular weight.

[0046] The heat sealing pressure is 270N, the time is 1 second, the temperature is set according to the test requirements, and the starting heat sealing temperature is tested (heat sealing strength ≥ 1.5N).

[0047] Determination of heat seal strength: Refer to QB / T23581998 test, test the corresponding initial heat seal strength and heat seal strength at the initial heat seal temperature and 110℃ heat seal temperature respectively. After heat sealing the sample, the width of the sample is (15±0.1) mm, the unfolded length is (100±1) mm, and the heat seal part is taken as the center, and it is opened 180°. The two ends of the sample are clamped on the two fixtures of the testing machine. The axis of the sample should coincide with the center line of the upper and lower fixtures, and the tightness should be appropriate to prevent the sample from slipping or breaking in the fixture before the test. The distance between the fixtures is 50 mm, the test speed is 300 mm / min, and the maximum load when the sample breaks is read.

[0048] The melting point was tested by DSC instrument under the conditions of 10K / min heating and cooling speed and 50mL / min N2 filling rate. The temperature was raised from 20°C to 200°C, then kept at 200°C for 2 minutes, then cooled from 200°C to 20°C, then kept at 20°C for 2 minutes, and finally raised from 20°C to 200°C.

[0049] For heat shrinkage test, cut 5 square specimens of 100mm*100mm from the sample to be tested in a direction parallel to the longitudinal direction. The side of the square should be parallel to the longitudinal direction of the film, and the transverse direction should be marked. Draw a line parallel to the side of the film and pass through the center of the square as a mark. Accurately measure the length of the straight line L0. Then place the sample flat on a stainless steel plate in a 120℃ constant temperature oven with the stainless steel plate located in the middle of the oven. During the test, blow air for 120s. Take out the sample, cool it to the test environment temperature, and measure the length of the transverse marked straight line L1.

[0050] Transverse heat shrinkage rate T=(L0-L1) / L0*100%.

[0051] It should be noted that the proportions described in the embodiments or comparative examples of the present invention are all weight percentages.

[0052] The preparation method of the modified ethylene-propylene binary copolymer polypropylene of the present invention comprises the following steps:

[0053] Weigh 1-5 mol% aluminum chloride of the total molar number of ethylene-propylene binary copolymer polypropylene and polyacrylic acid, dissolve it in an appropriate amount of dry dichloromethane, slowly dissolve it under stirring, and prepare an initiator solution. Add 30-50wt% polyacrylic acid and 50-70wt% ethylene-propylene binary copolymer polypropylene after drying, and add them to the reactor. Then add an appropriate amount of dry dichloromethane to control the concentration of the polymer in the solvent to 10-30wt%, and stir to form a uniform solution. Under stirring, slowly add the prepared initiator solution dropwise to the polymer solution, and control the reaction temperature to 20-40°C. The reaction time is 6-24 hours. After the reaction is completed, slowly add 5%-10% of the volume of the reaction system methanol as a terminator to the reaction system. Centrifuge, precipitate, filter, wash, and dry the mixed solution after the reaction to obtain ethylene-propylene binary copolymer polypropylene-g-polyacrylic acid copolymer, that is, modified ethylene-propylene binary copolymer polypropylene.

[0054] The method for preparing the modified homopolypropylene of the present invention comprises the following steps:

[0055] Weigh 1-5 mol% aluminum chloride of the total molar number of homopolypropylene and polyacrylic acid, dissolve it in an appropriate amount of dry dichloromethane, slowly dissolve it under stirring, and prepare an initiator solution. Add 30-50wt% polyacrylic acid and 50-70wt% homopolypropylene after drying and add them to the reactor. Then add an appropriate amount of dry dichloromethane to control the concentration of the polymer in the solvent to 10-30wt%, and stir to form a uniform solution. Under stirring, slowly add the prepared initiator solution dropwise to the polymer solution, and control the reaction temperature to 20-40°C. The reaction time is 6-24 hours. After the reaction is completed, 5%-10% of the volume of the reaction system methanol is slowly added to the reaction system as a terminator. The mixed solution after the reaction is centrifuged, precipitated, filtered, washed, and dried to obtain a homopolypropylene-g-polyacrylic acid copolymer, that is, a modified homopolypropylene.

[0056] The modified ethylene-propylene binary copolymer polypropylene and modified homopolymer polypropylene prepared by the above method have a polyacrylic acid grafting rate within a suitable range, which is beneficial to ensure the adsorption of low molecular weight substances.

[0057] Example 1

[0058] The present embodiment provides a BOPP laser film with a stable aluminum layer surface tension, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The method for preparing the resin layers of the BOPP laser film with a stable aluminum layer surface tension of the present embodiment comprises the following steps:

[0059] Preparation of molding layer resin: Take 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000 g / mol, number average molecular weight 45000 g / mol, molecular weight distribution index 4.4, initial heat sealing temperature 130°C, melting point 140°C, melt index 7g / 10min) and 4.0wt% anti-blocking masterbatch and mix them evenly to obtain molding layer resin.

[0060] Preparation of the upper surface layer resin: Take 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 116°C, melting point 138°C, melt index 7g / 10min) to obtain the upper surface layer resin.

[0061] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0062] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0063] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0064] The preparation method of the BOPP film of this embodiment comprises the following steps:

[0065] The raw materials are screened, and each layer of resin is stirred evenly according to the ratio. After metering, the materials are dropped into the extruders of each layer to form a homogenized melt. The melt passes through the filter and then is co-extruded through the die head. Among them, the melt extrusion temperature of the molded layer is: 200℃~250℃; the melt extrusion temperature of the upper surface layer is: 200~220℃; the melt extrusion temperature of the core layer is: 240℃~270℃; the melt extrusion temperature of the lower surface layer is 240-270℃; the melt extrusion temperature of the lower surface layer is: 240℃~270℃; according to the flat film method, the film is cast and then chilled into a thick film by a chilling roller. , wherein the temperature of the chilling water and the chilling roller is 15℃~50℃, and the thick film is stretched biaxially by longitudinal stretching first and then transverse stretching, wherein the temperature of the longitudinal stretching zone (molding layer) is 110℃~120℃; the longitudinal stretching temperature (lower surface layer) is 135℃~155℃; the transverse stretching zone temperature is 140℃~180℃; the longitudinal stretching ratio is 4.8 times; the transverse stretching ratio is 7.0 times, and a biaxially stretched film is made. After cooling, the film is subjected to corona treatment, flame treatment or plasma treatment, and then rolled into a mother roll. After aging treatment, it is slit into finished products.

[0066] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0067] Example 2

[0068] The present embodiment provides a BOPP laser film with a stable aluminum layer surface tension, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The method for preparing the resin layers of the BOPP laser film with a stable aluminum layer surface tension of the present embodiment comprises the following steps:

[0069] Preparation of molding layer resin: 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 250000g / mol, number average molecular weight 60000 g / mol, molecular weight distribution index 4.2, initial heat sealing temperature 131℃, melting point 141℃, melt index 6.5g / 10min) and 4.0wt% anti-blocking masterbatch were uniformly mixed to obtain molding layer resin. Preparation of upper surface layer resin: 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 116℃, melting point 138℃, melt index 7g / 10min) was taken to obtain upper surface layer resin.

[0070] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0071] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0072] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0073] The method for preparing the BOPP laser film with stable aluminum layer surface tension in this embodiment is basically the same as that in Embodiment 1, so it will not be described in detail.

[0074] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0075] Example 3

[0076] The present embodiment provides a BOPP laser film with a stable aluminum layer surface tension, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The method for preparing the resin layers of the BOPP laser film with a stable aluminum layer surface tension of the present embodiment comprises the following steps:

[0077] Preparation of molding layer resin: 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 150000g / mol, number average molecular weight 30000 g / mol, molecular weight distribution index 5.0, initial heat sealing temperature 128℃, melting point 137℃, melt index 8g / 10min) and 4.0wt% anti-blocking masterbatch were uniformly mixed to obtain molding layer resin. Preparation of upper surface layer resin: 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 117℃, melting point 140℃, melt index 6g / 10min) was taken to obtain upper surface layer resin.

[0078] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0079] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0080] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0081] The method for preparing the BOPP laser film with stable aluminum layer surface tension in this embodiment is basically the same as that in Embodiment 1, so it will not be described in detail.

[0082] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0083] Example 4

[0084] The present embodiment provides a BOPP laser film with a stable aluminum layer surface tension, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The method for preparing the resin layers of the BOPP laser film with a stable aluminum layer surface tension of the present embodiment comprises the following steps:

[0085] Preparation of molding layer resin: 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000g / mol, number average molecular weight 50000 g / mol, molecular weight distribution index 4.0, initial heat sealing temperature 132℃, melting point 140℃, melt index 6g / 10min) and 4.0wt% anti-adhesion masterbatch were uniformly mixed to obtain molding layer resin. Preparation of upper surface layer resin: 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 115℃, melting point 135℃, melt index 8g / 10min) was taken to obtain upper surface layer resin.

[0086] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0087] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 170°C, melt index 2g / 10min) to obtain the next surface layer resin.

[0088] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0089] The method for preparing the BOPP laser film with stable aluminum layer surface tension in this embodiment is basically the same as that in Embodiment 1, so it will not be described in detail.

[0090] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0091] Example 5

[0092] The present embodiment provides a BOPP laser film with a stable aluminum layer surface tension, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The method for preparing the resin layers of the BOPP laser film with a stable aluminum layer surface tension of the present embodiment comprises the following steps:

[0093] Preparation of molding layer resin: 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000g / mol, number average molecular weight 45000 g / mol, molecular weight distribution index 4.4, initial heat sealing temperature 130℃, melting point 140℃, melt index 7g / 10min) and 4.0wt% anti-blocking masterbatch were uniformly mixed to obtain molding layer resin. Preparation of upper surface layer resin: 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 40%, initial heat sealing temperature 117℃, melting point 140℃, melt index 6g / 10min) was taken to obtain upper surface layer resin.

[0094] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0095] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 40%, melting point 180°C, melt index 2g / 10min) to obtain the next surface layer resin.

[0096] Preparation of lower surface layer resin: Take 100wt% homopolymer polypropylene to obtain lower surface layer resin.

[0097] The method for preparing the BOPP laser film with stable aluminum layer surface tension in this embodiment is basically the same as that in Embodiment 1, so it will not be described in detail.

[0098] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0099] Example 6

[0100] The present embodiment provides a BOPP laser film with a stable aluminum layer surface tension, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The method for preparing the resin layers of the BOPP laser film with a stable aluminum layer surface tension of the present embodiment comprises the following steps:

[0101] Preparation of molding layer resin: 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000g / mol, number average molecular weight 45000 g / mol, molecular weight distribution index 4.4, initial heat sealing temperature 130℃, melting point 140℃, melt index 7g / 10min) and 4.0wt% anti-adhesion masterbatch were uniformly mixed to obtain molding layer resin. Preparation of upper surface layer resin: 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 25%, initial heat sealing temperature 117℃, melting point 140℃, melt index 6g / 10min) was taken to obtain upper surface layer resin.

[0102] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0103] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 25%, melting point 180°C, melt index 2g / 10min) to obtain the next surface layer resin.

[0104] Preparation of lower surface layer resin: 94.0 wt% homopolymer polypropylene and 6.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0105] The method for preparing the BOPP laser film with stable aluminum layer surface tension in this embodiment is basically the same as that in Embodiment 1, so it will not be described in detail.

[0106] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0107] Example 7

[0108] The present embodiment provides a BOPP laser film with a stable aluminum layer surface tension, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The method for preparing the resin layers of the BOPP laser film with a stable aluminum layer surface tension of the present embodiment comprises the following steps:

[0109] Preparation of molding layer resin: 94.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000g / mol, number average molecular weight 45000 g / mol, molecular weight distribution index 4.4, initial heat sealing temperature 130℃, melting point 140℃, melt index 7g / 10min) and 6.0wt% anti-blocking masterbatch were uniformly mixed to obtain molding layer resin. Preparation of upper surface layer resin: 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 116℃, melting point 138℃, melt index 7g / 10min) was taken to obtain upper surface layer resin.

[0110] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0111] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0112] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0113] The method for preparing the BOPP laser film with stable aluminum layer surface tension in this embodiment is basically the same as that in Embodiment 1, so it will not be described in detail.

[0114] The total thickness of the film is 18µm, of which the molded layer thickness is 0.7µm, the upper surface layer thickness is 0.9µm, the lower surface layer thickness is 0.9µm, and the lower surface layer thickness is 1.2µm.

[0115] Example 8

[0116] The present embodiment provides a BOPP laser film with a stable aluminum layer surface tension, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The method for preparing the resin layers of the BOPP laser film with a stable aluminum layer surface tension of the present embodiment comprises the following steps:

[0117] Preparation of molding layer resin: 98.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000g / mol, number average molecular weight 45000g / mol, molecular weight distribution index 4.4, initial heat sealing temperature 130℃, melting point 140℃, melt index 7g / 10min) and 2.0wt% anti-adhesion masterbatch were uniformly mixed to obtain molding layer resin. Preparation of upper surface layer resin: 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 116℃, melting point 138℃, melt index 7g / 10min) was taken to obtain upper surface layer resin.

[0118] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0119] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0120] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0121] The method for preparing the BOPP laser film with stable aluminum layer surface tension in this embodiment is basically the same as that in Embodiment 1, so it will not be described in detail.

[0122] The total thickness of the film is 18µm, of which the molded layer thickness is 0.9µm, the upper surface layer thickness is 0.7µm, the lower surface layer thickness is 0.7µm, and the lower surface layer thickness is 1.5µm.

[0123] Comparative Example 1

[0124] This comparative example provides a BOPP laser film, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The preparation method of each layer of resin of the BOPP laser film of this comparative example comprises the following steps:

[0125] Preparation of molding layer resin: Take 100wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 210000 g / mol, number average molecular weight 30000 g / mol, molecular weight distribution index 7.0, initial heat sealing temperature 125°C, melting point 139°C, melt index 8g / 10min) to obtain molding layer resin.

[0126] Preparation of the upper surface layer resin: Take 100.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 210000g / mol, number average molecular weight 30000, molecular weight distribution index 7.0, initial heat sealing temperature 125°C, melting point 139°C, melt index 8g / 10min) to obtain the upper surface layer resin.

[0127] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0128] Preparation of the next surface layer resin: Take 100.0wt% homopolymer polypropylene to obtain the next surface layer resin.

[0129] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0130] The preparation method of the BOPP laser film of this comparative example is basically the same as the preparation method of the BOPP laser film with stable aluminum layer surface tension in Example 1, so it will not be described in detail.

[0131] The total thickness of the film is 18µm, of which the molded layer thickness is 0.9µm, the upper surface layer thickness is 0.7µm, the lower surface layer thickness is 0.7µm, and the lower surface layer thickness is 1.5µm.

[0132] The BOPP laser film of this comparative example is easily degraded to produce low molecular weight substances after corona treatment, and the corona decays quickly.

[0133] Comparative Example 2

[0134] This comparative example provides a BOPP laser film, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The preparation method of each layer of resin of the BOPP laser film of this comparative example comprises the following steps:

[0135] Preparation of molding layer resin: Take 100wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 140000 g / mol, number average molecular weight 20000 g / mol, molecular weight distribution index 7.0, initial heat sealing temperature 122°C, melting point 136°C, melt index 9g / 10min) to obtain molding layer resin.

[0136] Preparation of the upper surface layer resin: Take 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 116°C, melting point 138°C, melt index 7g / 10min) to obtain the upper surface layer resin.

[0137] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0138] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0139] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0140] The preparation method of the BOPP laser film of this comparative example is basically the same as the preparation method of the BOPP laser film with stable aluminum layer surface tension in Example 1, so it will not be described in detail.

[0141] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0142] The BOPP laser film in this comparative example has relatively large transverse heat shrinkage and haze, is easily degraded to produce low-molecular substances after corona treatment, and has fast corona decay.

[0143] Comparative Example 3

[0144] This comparative example provides a BOPP laser film, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The preparation method of each layer of resin of the BOPP laser film of this comparative example comprises the following steps:

[0145] Preparation of molding layer resin: Take 100wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 300000 g / mol, number average molecular weight 100000 g / mol, molecular weight distribution index 3.0, initial heat sealing temperature 133°C, melting point 139°C, melt index 5g / 10min) to obtain molding layer resin.

[0146] Preparation of the upper surface layer resin: Take 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 116°C, melting point 138°C, melt index 7g / 10min) to obtain the upper surface layer resin.

[0147] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0148] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0149] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0150] The preparation method of the BOPP laser film of this comparative example is basically the same as the preparation method of the BOPP laser film with stable aluminum layer surface tension in Example 1, so it will not be described in detail.

[0151] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0152] The BOPP laser film of this comparative example is broken continuously during production.

[0153] Comparative Example 4

[0154] This comparative example provides a BOPP laser film, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The preparation method of each layer of resin of the BOPP laser film of this comparative example comprises the following steps:

[0155] Preparation of molding layer resin: Take 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000 g / mol, number average molecular weight 45000 g / mol, molecular weight distribution index 4.4, initial heat sealing temperature 130°C, melting point 140°C, melt index 7g / 10min) and 4.0wt% anti-blocking masterbatch and mix them evenly to obtain molding layer resin.

[0156] Preparation of the upper surface layer resin: Take 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 50%, initial heat sealing temperature 116°C, melting point 138°C, melt index 7g / 10min) to obtain the upper surface layer resin.

[0157] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0158] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 50%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0159] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0160] The preparation method of the BOPP laser film of this comparative example is basically the same as the preparation method of the BOPP laser film with stable aluminum layer surface tension in Example 1, so it will not be described in detail.

[0161] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0162] The BOPP laser film of this comparative example has a relatively large transverse heat shrinkage rate because the grafting rate of polyacrylic acid in the modified ethylene-propylene binary copolymer polypropylene and the modified homopolymer polypropylene is too high.

[0163] Comparative Example 5

[0164] This comparative example provides a BOPP laser film, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The preparation method of each layer of resin of the BOPP laser film of this comparative example comprises the following steps:

[0165] Preparation of molding layer resin: Take 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000 g / mol, number average molecular weight 45000 g / mol, molecular weight distribution index 4.4, initial heat sealing temperature 130°C, melting point 140°C, melt index 7g / 10min) and 4.0wt% anti-blocking masterbatch and mix them evenly to obtain molding layer resin.

[0166] Preparation of the upper surface layer resin: Take 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 20%, initial heat sealing temperature 116°C, melting point 138°C, melt index 7g / 10min) to obtain the upper surface layer resin.

[0167] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0168] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 20%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0169] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0170] The preparation method of the BOPP laser film of this comparative example is basically the same as the preparation method of the BOPP laser film with stable aluminum layer surface tension in Example 1, so it will not be described in detail.

[0171] The total thickness of the film is 18µm, of which the molded layer thickness is 0.8µm, the upper surface layer thickness is 0.8µm, the lower surface layer thickness is 0.8μm, and the lower surface layer thickness is 1.3μm.

[0172] The BOPP laser film of this comparative example cannot effectively adsorb low molecular weight substances because the grafting rates of polyacrylic acid in the modified ethylene-propylene binary copolymer polypropylene and the modified homopolymer polypropylene are too low.

[0173] Comparative Example 6

[0174] This comparative example provides a BOPP laser film, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The preparation method of each layer of resin of the BOPP laser film of this comparative example comprises the following steps:

[0175] Preparation of molding layer resin: Take 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000 g / mol, number average molecular weight 45000 g / mol, molecular weight distribution index 4.4, initial heat sealing temperature 130°C, melting point 140°C, melt index 7g / 10min) and 4.0wt% anti-blocking masterbatch and mix them evenly to obtain molding layer resin.

[0176] Preparation of the upper surface layer resin: Take 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 116°C, melting point 138°C, melt index 7g / 10min) to obtain the upper surface layer resin.

[0177] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0178] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0179] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0180] The preparation method of the BOPP laser film of this comparative example is basically the same as the preparation method of the BOPP laser film with stable aluminum layer surface tension in Example 1, so it will not be described in detail.

[0181] The total thickness of the film is 18µm, of which the molded layer thickness is 1.1µm, the upper surface layer thickness is 0.5µm, the lower surface layer thickness is 0.8µm, and the lower surface layer thickness is 1.3µm.

[0182] The BOPP laser film in this comparative example has a too small upper surface thickness, and the thickness of the molding layer and the upper surface layer are not properly matched, resulting in an initial heat-sealing temperature of the finished laser film being too high, affecting the molding effect.

[0183] Comparative Example 7

[0184] This comparative example provides a BOPP laser film, comprising a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer arranged in sequence. The preparation method of each layer of resin of the BOPP laser film of this comparative example comprises the following steps:

[0185] Preparation of molding layer resin: Take 96.0wt% ethylene-propylene copolymer polypropylene (weight average molecular weight 200000 g / mol, number average molecular weight 45000 g / mol, molecular weight distribution index 4.4, initial heat sealing temperature 130°C, melting point 140°C, melt index 7g / 10min) and 4.0wt% anti-blocking masterbatch and mix them evenly to obtain molding layer resin.

[0186] Preparation of the upper surface layer resin: Take 100.0wt% modified ethylene-propylene copolymer polypropylene (polyacrylic acid grafting rate 35%, initial heat sealing temperature 116°C, melting point 138°C, melt index 7g / 10min) to obtain the upper surface layer resin.

[0187] Preparation of core layer resin: 100.0wt% homopolymer polypropylene is taken to obtain core layer resin.

[0188] Preparation of the next surface layer resin: Take 100.0wt% of modified homopolypropylene (polyacrylic acid grafting rate 35%, melting point 175°C, melt index 3g / 10min) to obtain the next surface layer resin.

[0189] Preparation of lower surface layer resin: 95.0 wt% homopolymer polypropylene and 5.0 wt% anti-blocking masterbatch were uniformly mixed to obtain lower surface layer resin.

[0190] The preparation method of the BOPP laser film of this comparative example is basically the same as the preparation method of the BOPP laser film with stable aluminum layer surface tension in Example 1, so it will not be described in detail.

[0191] The total thickness of the film is 18µm, of which the molded layer thickness is 0.4µm, the upper surface layer thickness is 1.2µm, the lower surface layer thickness is 0.8µm, and the lower surface layer thickness is 1.3µm.

[0192] The BOPP laser film in this comparative example cannot be stretched smoothly because the surface layer is too thick, resulting in continuous film breakage during production.

[0193] The performance test results of the BOPP laser films with stable surface tension of the aluminum layer of Examples 1 to 8 are shown in Table 1 below, and the performance test results of the BOPP laser films with stable surface tension of the aluminum layer of Comparative Examples 1 to 7 are shown in Table 2 below.

[0194] Table 1

[0195]

[0196] Table 2

[0197]

[0198] Comparative Example 1 is a general laser film. It can be seen from Comparative Examples 1, 2 and 3 that the weight average molecular weight, number average molecular weight and molecular weight distribution index of ethylene-propylene binary copolymer polypropylene will have a certain influence on the initial heat sealing temperature, melting point and melt index of ethylene-propylene binary copolymer polypropylene, thereby affecting the haze of the BOPP laser film and the attenuation rate of the surface tension of the aluminum layer, and even causing the film to be unable to be produced normally.

[0199] It can be seen from Comparative Examples 4, 5, 6 and 7 that the grafting rate of polyacrylic acid and the thickness of the sub-surface layer will have a certain impact on the heat shrinkage rate and production smoothness of the finished product, thereby affecting the surface tension attenuation of the aluminum layer of the BOPP laser film, and even causing the film to be unable to be produced normally or unable to be processed downstream.

[0200] In summary, the stable production of BOPP laser film with stable aluminum layer surface tension, low haze and low thermal shrinkage requires the synergistic effect of multiple factors.

[0201] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A BOPP laser film with stable aluminum layer surface tension, characterized in that: The invention comprises a molded layer, an upper surface layer, a core layer, a lower surface layer and a lower surface layer which are arranged in sequence; the molded layer comprises ethylene-propylene binary copolymer polypropylene, the molecular weight distribution index of the ethylene-propylene binary copolymer polypropylene is 4-5, the molecular weight distribution index=weight average molecular weight / number average molecular weight, the upper surface layer is composed of 100.0wt% modified ethylene-propylene binary copolymer polypropylene, the modified ethylene-propylene binary copolymer polypropylene comprises ethylene-propylene binary copolymer polypropylene-g-polyacrylic acid copolymer, the modified ethylene-propylene binary copolymer polypropylene is composed of the ethylene-propylene binary copolymer polypropylene and polyacrylic acid The modified homopolypropylene is prepared by ion grafting copolymerization, the grafting rate of the polyacrylic acid in the modified ethylene-propylene binary copolymer polypropylene is 25-40%, the core layer includes homopolypropylene, the lower surface layer is composed of 100.0wt% modified homopolypropylene, the modified homopolypropylene includes homopolypropylene-g-polyacrylic acid copolymer, the modified homopolypropylene is prepared by ion grafting copolymerization of the homopolypropylene and polyacrylic acid, the grafting rate of the polyacrylic acid in the modified homopolypropylene is 25-40%, and the lower surface layer includes homopolypropylene.

2. The BOPP laser film with stable aluminum layer surface tension according to claim 1, characterized in that: The thickness of the upper surface layer and the lower surface layer are both 0.7-0.9 μm, and the thickness of the molded layer is 0.7-0.9 μm.

3. The BOPP laser film with stable aluminum layer surface tension according to claim 1, characterized in that: The weight average molecular weight of the ethylene-propylene binary copolymer polypropylene is 150,000-250,000 g / mol.

4. The BOPP laser film with stable aluminum layer surface tension according to claim 1, characterized in that: The number average molecular weight of the ethylene-propylene binary copolymer polypropylene is 30000-60000 g / mol.

5. The BOPP laser film with stable aluminum layer surface tension according to claim 1, characterized in that: Under the measuring conditions of 2.16kg and 230°C, the melt index of the EPDM and the modified EPDM are both 6-8g / 10min, the melting point of the EPDM is 138-142°C, and the melting point of the modified EPDM is 135-140°C.

6. The BOPP laser film with stable aluminum layer surface tension according to claim 1, characterized in that: The melting point of the modified homopolypropylene is 170-180° C., and the melt index of the modified homopolypropylene is 2-4 g / 10 min as measured under the conditions of 2.16 kg and 230° C.

7. The BOPP laser film with stable aluminum layer surface tension according to claim 1, characterized in that: The initial heat-sealing temperature of the ethylene-propylene binary copolymer polypropylene is 128-132° C., and the initial heat-sealing temperature of the modified ethylene-propylene binary copolymer polypropylene is 115-117° C.

8. A method for preparing a BOPP laser film with a stable aluminum layer surface tension as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials are screened, and each layer of raw materials is stirred evenly according to the ratio. After metering, the raw materials are dropped into the extruder to form a homogenized melt. The melt passes through a filter and then is co-extruded through a die head. According to the flat film method, the cast sheet is chilled into a thick sheet. The thick sheet is made into a biaxially stretched film by a biaxial stretching method of first longitudinal stretching and then transverse stretching. After cooling, the film is subjected to corona treatment, flame treatment or plasma treatment, and then rolled into a mother roll. After aging treatment, it is slit into a finished product.